Retarding Basin Design As Flood Countermeasures at Cicendo Bandung City - Wahyu Al'amin; Yati Muliati (Department of Civil Engineering, Faculty of Engineering, Universitas Brawijaya, 2023)
The current solution Bandung City Government do to avoiding flood was building the retarding basin. The purpose of this research was to plan the retention basin’s discharge, volume and area. This research was conducted on Bima Street, Cicendo which is drained by Citepus River. The research data includes rainfall data from five rain posts, maps and existing river conditions. The analysis contains catchment area made from ArcGis program which result are 40 km2. Hydrological analysis produces the planned rain discharge for 100 years return period which is 20,22658 m3/s. Hydraulics analysis which is finding the discharge river existing. Basin discharge acquired from differences between rain discharge and river discharge then plan for inlet and outlet doors. Total capacity of retarding basin was 4360,5 m3. Inlet and outlet doors are planned each two doors with 2 meters width and 1 meter height.